Impact of Weather on Sigatoka Leaf Spot of Banana (Musa spp. L.) and its Ecofriendly Management (The Agriculturists, 2016)
A study was carried out during July 2010 to April 2012 to understand the effect of weather prevalence on sigatoka disease of banana suckers in different areas of Bangladesh and to develop an environment friendly disease management practice.  Four locations viz. Dinajpur, Bogra, Rangpur and Madhupur were surveyed. To find out suitable and ecofriendly management practices for  controlling sigatoka disease of banana, seven  treatments were used viz. i) Soil drenching with BAU- Biofungicide (2%), ii) BAU-Biofungicide as foliar spray (2%), iii) Soil drenching with BAU-Biofungicide (2%) plus foliar spray (2%), iv) Bavistin (carbendazim) spray (0.2%), v) Dithane M-45 (mancozeb) spray (0.2%), vi) Soil drenching with BAU-Biofungicide (2%) plus Bavistin spray (0.2%); and vii) control. The average highest incidence (26.42%) and severity (22.84%) of sigatoka disease of banana suckers were recorded during October at Bogra, while the lowest incidence (9.75 %) and severity (8.51%) were recorded during January at Dinajpur. Out of the control measures employed, BAU-Biofungicide (2%) either alone or in combination with Bavistin (0.2%) was found as an excellent biocontrol means for controlling sigatoka disease of banana suckers.DOI: http://dx.doi.org/10.3329/agric.v13i2.26587The Agriculturists 2015; 13(2) 44-53